2011
DOI: 10.1074/jbc.m110.190546
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin (Apolipoprotein J), a Molecular Chaperone That Facilitates Degradation of the Copper-ATPases ATP7A and ATP7B

Abstract: The copper-transporting P 1B -type ATPases (Cu-ATPases) ATP7A and ATP7B are key regulators of physiological copper levels. They function to maintain intracellular copper homeostasis by delivering copper to secretory compartments and by trafficking toward the cell periphery to export excess copper. Mutations in the genes encoding ATP7A and ATP7B lead to copper deficiency and toxicity disorders, Menkes and Wilson diseases, respectively. This report describes the interaction between the Cu-ATPases and clusterin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 39 publications
(52 reference statements)
4
43
1
Order By: Relevance
“…2B). These results are in contrast to our previous data, which demonstrated that clusterin interacted to a greater extent with ATP7A and ATP7B when cells were treated with the same oxidizing agents (15). The data presented here suggests that COMMD1 interaction with the Cu-ATPases occurs in response to different cellular signals compared with clusterin.…”
Section: Atp7b Clusterin and Commd1 Exist In A Complex-co-contrasting
confidence: 56%
See 4 more Smart Citations
“…2B). These results are in contrast to our previous data, which demonstrated that clusterin interacted to a greater extent with ATP7A and ATP7B when cells were treated with the same oxidizing agents (15). The data presented here suggests that COMMD1 interaction with the Cu-ATPases occurs in response to different cellular signals compared with clusterin.…”
Section: Atp7b Clusterin and Commd1 Exist In A Complex-co-contrasting
confidence: 56%
“…1, A and B) verified that endogenous ATP7B interacts with both clusterin and COMMD1 in mammalian cells as previously reported (15)(16)(17). The anti-ATP7B antibody immunoprecipitated ATP7B, clusterin, and COMMD1, whereas preimmune serum did not precipitate these proteins (Fig.…”
Section: Atp7b Clusterin and Commd1 Exist In A Complex-co-supporting
confidence: 54%
See 3 more Smart Citations